ANALISIS KELIMPAHAN BIVALVIA DI KAWASAN BLOK JATI PAPAK TAMAN NASIONAL ALAS PURWO DAN KONTRIBUSINYA TERHADAP PEREKONOMIAN LOKAL - Kurniawan, Ridho (JURNAL BIOSENSE, 2025)
Alas Purwo National Park in Banyuwangi Regency possesses extensive mangrove forests, including Pangpang Bay Kucur Resort in the Jati Papak Block. This mangrove ecosystem serves as habitat for various marine organisms, including Bivalvia. This research was conducted from November to December 2024, aiming to analyze abundance, identify Bivalvia species, and assess their contribution to the local community's economy, particularly shellfish collectors. The research employed purposive sampling through transects and plotting. Sampling locations were divided into three stations: Mangrove Trail, Ngaseman, and Curah Wuluh, with each station containing four transects, and each transect having 5 plots of 2 × 2 m in size, with 5-meter distances between transects and plots. Measured abiotic parameters included temperature, salinity, and pH. The research found 11 species from 8 families, with Isognomon ephippium and Brachidontes exustus being the dominant species with very high abundance. The species diversity index was classified as low, with the highest value at station 3 (0.724) and the lowest at station 1 (0.716). Socio-economically, Bivalvia contributes as a food source and seasonal income for surrounding communities, especially during low tide. This research emphasizes the importance of sustainable management to maintain the stability of mangrove ecosystems as habitat for marine organisms, particularly Bivalvia, and to improve the welfare of local communities.